2008
DOI: 10.3892/or.19.5.1265
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of tumor-specific CD8+ CTLs and anti-CD25 mAb provide improved immunotherapy

Abstract: One new approach to cancer therapy is based on the adoptive transfer of tumor-specific cytotoxic T cells and anti-CD25 antibodies. In the present study, CD8 + and IFN-γ secreting T lymphocytes (CTLs) were enriched as tumorspecific cytotoxic T cells from spleen lymphocytes of mice bearing the Renca tumor (a murine renal carcinoma line originating from a BALB/c mouse) after stimulation with tumor cells. An anti-CD25 IL-2Rα(anti-CD25) mAb from hybridoma PC61 was used for depletion for CD4 + CD25 + regulatory T (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…21,22 However, the efficacy of adoptive transfer of TILs is limited. 23,24 One important factor is bulk TILs are heterogeneous, which contain various lymphocyte subsets with different immune functions. Some of the subsets such as Treg participate in tumor-induced immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 However, the efficacy of adoptive transfer of TILs is limited. 23,24 One important factor is bulk TILs are heterogeneous, which contain various lymphocyte subsets with different immune functions. Some of the subsets such as Treg participate in tumor-induced immune suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the increased number of Treg cells in the peripheral blood and TILs in patients with ovarian, gastric or esophageal cancer could impair cell-mediated immunity and promote disease progression (Morse et al, 2008). Previous studies have demonstrated that removing or suppressing Treg cells can strengthen antitumor immunity (Ohmura et al, 2008;Setiady et al, 2010), and these studies indicate that Treg cells play a negative regulatory role in human antitumor immunity. In our study, we showed an increased numbers of CD4+CD25+Foxp3+ T cells in the TILs of HCC, which are inconsistence with previous results.…”
Section: Discussionmentioning
confidence: 85%
“…Considered that tumorreactive Cytotoxic CD4+ T cells have been a bright point in immunotherapy of tumor (Porakishvili et al, 2001;Quezada et al, 2010;Akhmetzyanova et al, 2013), so we also measured perforin production of CD8+ T cells as well as CD4+ T cells. Unfortunately, CPT showed marginal effect on CD8+ cytotoxic T cells, even though that CD8+ cytotoxic T cells are classic tumor killing cells (Ohmura et al, 2008), but enhanced perforin production of CD4+ T cells. To further verify this result, we isolated CD4+ and CD8+ T cells from tumor-bearing mice and analyzed their cytotoxic ability, results same with in vivo data.…”
Section: Discussionmentioning
confidence: 99%